2015
DOI: 10.3390/biology4040785
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Differentiating Prion Types in Food-Producing Animals

Abstract: Prions are an enigma amongst infectious disease agents as they lack a genome yet confer specific pathologies thought to be dictated mainly, if not solely, by the conformation of the disease form of the prion protein (PrPSc). Prion diseases affect humans and animals, the latter including the food-producing ruminant species cattle, sheep, goats and deer. Importantly, it has been shown that the disease agent of bovine spongiform encephalopathy (BSE) is zoonotic, causing variant Creutzfeldt Jakob disease (vCJD) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 118 publications
(193 reference statements)
0
4
0
1
Order By: Relevance
“…In humans, the symptoms of prion diseases are quite similar to the ones observed in animals. In addition, other symptoms observed in humans such as intellectual and memory loss, muscle atrophy, and increasing loss of brain function were also observed in prion diseases in animals (Gough, 2015).…”
Section: Prion Diseases In Animalsmentioning
confidence: 95%
“…In humans, the symptoms of prion diseases are quite similar to the ones observed in animals. In addition, other symptoms observed in humans such as intellectual and memory loss, muscle atrophy, and increasing loss of brain function were also observed in prion diseases in animals (Gough, 2015).…”
Section: Prion Diseases In Animalsmentioning
confidence: 95%
“…Some studies have identified a larger molecular mass of the unglycosylated band of PrP res in sheep with natural scrapie than in experimentally BSE-infected sheep ( Figure 5 ). An unglycosylated band of PrP res in BSE sheep is approximately 1.6 kDa smaller than in sheep scrapie [ 6 , 21 , 53 , 77 , 78 , 79 , 80 , 81 ]. Unfortunately, the unglycosylated fraction represents only 5–20% of total PrP res , and the unglycosylated band can be very faint or invisible, making this approach less attractive for routine diagnosis.…”
Section: Western Blot Methodsmentioning
confidence: 99%
“…The P4 antibody that recognizes the N-terminal end of the protein binds well only to PrP res in scrapie and almost not at all to PrP res in sheep with BSE. In contrast, monoclonal antibodies 6H4, 66.94b4, 505, 8G8, and R521, recognize the core region, and bind PrP res in samples from both BSE- and scrapie-infected sheep; thus, WB with double antibody discrimination can easily distinguish BSE and scrapie [ 6 , 8 , 75 , 79 ]. Furthermore, the ratio of P4/core antibody is significantly higher for scrapie than for BSE [ 16 , 53 , 78 , 82 ].…”
Section: Western Blot Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…O príon (PrPc), quando é mal dobrado, ele perde sua função e se torna PrPSc, que é o príon patogênico. Quando patogênico, ele deixa suas funções fisiológicas de lado e se torna tóxico para as células do sistema nervoso central (SNC), tendo como consequência patologias cerebrais características incluindo: espongiose no cérebro, astrocitose e também uma perda neuronal, ambas associadas a essas doenças (GOUGH et al, 2015).…”
Section: Revisão De Literaturaunclassified